Biofluid Markers for Prodromal Parkinson's Disease: Evidence From a Catecholaminergic Perspective - Vermeiren, Yannick; Hirschberg, Yael; Mertens, Inge; De Deyn, Peter P. (Frontiers in Neurology, 2020)
Parkinson’s disease (PD) is the most frequent of all Lewy body diseases, a family of progressive neurodegenerative disorders characterized by intraneuronal cytoplasmic inclusions of α-synuclein. Its most defining features are bradykinesia, tremor, rigidity and postural instability. By the time PD manifests with motor signs, 70% of dopaminergic midbrain neurons are lost, and the disease is already in the middle or late stage. However, there are various non-motor symptoms occurring up to 20 years before the actual parkinsonism that are closely associated with profound deficiency of myocardial noradrenaline content and peripheral sympathetic denervation, as evidenced by neuroimaging experiments in recent years. Additionally, there is an inherent autotoxicity of catecholamines in the neuronal cells in which they are produced, forming toxic catecholaldehyde intermediates that make α-synuclein prone to aggregation, initiating a cascade of events that ultimately leads to neuronal death. The etiopathogenesis of PD and related synucleinopathies thus may well be a prototypical example of a catecholamine-regulated neurodegeneration, given that the synucleinopathy in PD spreads in synergy with central and peripheral catecholaminergic dysfunction from the earliest phases onwards. That is why catecholamines, their metabolites, precursors or derivatives in cerebrospinal fluid or plasma could be of particular interest as biomarkers for prodromal and de novo PD. Because there is great demand for such markers, this mini-review summarizes all catecholamine-related studies to date, in addition to providing profound neurochemical evidence on a systemic and cellular level to further emphasize this hypothesis, and, with emphasis on extracellular vesicles as a novel diagnostic and therapeutic incentive.